Forgery and Fraud Offenses in Romanian Law - Rusu, Ion; Birzu, Bogdan; Rusu, Ioana (Acta Universitatis Danubius. Juridica, 2021)
The present paper is a brief analysis of the crimes included in the group of counterfeiters in Romanian law. In the analysis, we have insisted on highlighting the tradition of incriminating this kind of deeds, a tradition that materialized in the provision of this group of crimes starting with the Criminal Code of 1864, continuing with the Criminal Code Charles II and the Criminal Code of 1969. Regardless of the political regime, the Romanian legislator continued to defend through criminal law these values, which in their essence led to increasing the trust of citizens in documents issued by state institutions or documents emanating from other entities. Out of the desire to present a paper through which we examine the current legal provisions, we have also considered highlighting the amendments and completions brought to some incriminating texts in Chapter I by Law no. 207/2021. The paper will be included in a criminal law course to be published in the future in volume IV at Universul Juridic Publishing House. Given the addressed topic, the paper may be useful to students of the country's faculties, as well as to practitioners in the field.